Biomass composition of phytoplanktons in Mahakali River, Nepal - Mahaseth, Vinod Kumar (Our Nature, 2017)
Phytoplankton biomass composition of Mahakali River has been studied. Samples were collected twice a month at an interval of 15 days for two years from September, 2003 to August, 2005. It was observed that the average annual biomass of phytoplankton community was 10.494 mg/m3 during the first year and 8.057 mg/m3 in the second year of the study. The peak of biomass was obtained in the month of May (15.276mg/m3) and March (11.183mg/m3) during the first and second year, respectively. The lowest values of biomass were recorded in the month of September (0.989mg/m3) and August (0.842mg/m3) during the respective years. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.